Assessing genetic population structure of permit (Trachinotus falcatus) between South Florida and Belize: movement towards inferring population health - Andrew J. Natter; Benjamin M. Binder; Diego Cardeñosa; Gina M. Clementi; Kevin A. Feldheim; Kirk R. Gastrich; Michael R. Heithaus; Kevin M. Boswell (Environmental Biology of Fishes, 2026)
Abstract Understanding population structure and connectivity is essential for effective fisheries management, particularly for wide-ranging marine species like permit ( Trachinotus falcatus ). We investigated the genetic structure and diversity of permit at ecologically important locations (e.g., nursery habitats and spawning sites) in South Florida and Southern Belize using mitochondrial Cytochrome Oxidase C Subunit I (COI) sequences. A total of 438 permit ( n = 338 Florida; n = 100 Belize) were collected, of which 401 yielded high quality DNA sequences, revealing 18 haplotypes, with one dominant haplotype (H1) present in over 80% of individuals across all sites. Haplotype diversity (0.0987–0.427 in Florida; 0.1837 in Belize) and nucleotide diversity (0.000168–0.00117 in Florida; 0.000401 in Belize) were low, and AMOVA results indicated that > 99% of genetic variation is described by variation among individuals of the same site groups, implying low population structure. Pairwise F ST values showed no significant genetic differentiation among Florida locations, as well as no differentiation between South Florida and Belize. These results support low population structure in Florida and across > 1000 km between Florida and Belize, suggesting extensive larval dispersal likely facilitated by regional ocean currents, with Belize potentially serving as a larval source for Florida. While high population connectivity may buffer against localized demographic declines, low genetic diversity and ongoing threats (e.g., habitat degradation, climate change, and fishing mortality) underscore the need for continued monitoring and protection of critical spawning sites, such as the seasonally closed Western Dry Rocks Marine Protected Area, offshore of Key West, Florida.